Effects of Paraquat and Alachlor on Soil Microorganisms in Peat Soil - Sahid, Ismail (1992)
A study was carried out to investigate the effects of alachlor and paraquat on microbial activities in peat soil. Effects of the herbicides on CO2 evolution and phosphatase activity were monitored for 12 weeks in ambient conditions. The results showed that paraquat and alachlor caused an initial increase in CO2 released and subsequently decreased after 53 days of incubation. Comparatively, more CO2 was released from the soil treated with alachlor than that treated with paraquat. An initial increase in phosphatase activity was observed for both herbicides but the level of activity was substantially reduced after 12 days of incubation. Fungal and bacterial populations in the soil were also affected by both herbicides. At 250 ppm, alachlor and paraquat caused a reduction in bacterial population of 78%and 95% respectively. Alachlor was shown to be more toxic to fungal populations in the soil than paraquat.